IMPROVED UNDERSTANDING OF PHOTO AND VIDEO COMPOSITION WITH PEER TEACHING METHOD - Indah Susanti (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
Mastering the field of photography and videography, especially in composition which contains how to arrange the elements to be visualized. These two fields of knowledge synergize in producing creative visualizations. Moreover, graduates from the broadcasting major are prepared to be ready to enter the industrial world. It also directly demands cameramen to increase their abilities, especially in the process of formation and education. This prompted researchers to observe the ability and understanding of photo and video composition of class XI PSPT SMKN 1 Six Lingkung, Padang Pariaman Regency. To increase this understanding, researchers used the peer teaching method. So far, in the PSPT Department this method has never been applied in increasing theoretical understanding to achieve quality work.